Assessing Undergraduate Student Nurses' Performance in Various Public Health Roles Using Simulation. Issue 3 (3rd July 2021) - McEwing, Evan; Placide-Reaves, Regine; Matsuda, Yui; Prather, Susan; Everett-Thomas, Ruth
ABSTRACT: Purpose : To expose students to various public health roles and complement clinical experience using simulated encounters. Design : This exploratory study assessed students' performance of basic nursing tasks for three public health nurse roles. Methods : 15-guided questions were used to evaluate a convenience sample of 137 students' expected performance compared to their actual performance of basic nursing skills. Findings : Students' performed well in all nurse roles with some significant differences in completing a few critical tasks in the case manager and school nurse roles. Conclusion : Simulation can address gaps in nursing programs and expose student nurses to various public health roles using real-life scenarios. Clinical Evidence : Lack of clinical sites in public health limits students' experience to a myriad of nurse functions within communities.